Peptídeos bioativos do Anuro Hypsiboas boans - Souza, Beatriz Blenda Pinheiro de (2015)
Amphibians are a large part of the global animals biodiversity. The order Anura stands out among amphibians for its diversity in many places in the world. The anuros immune system based on the expression, production, accumulation and release of secretions containing biologically active substances is a major defense strategie developed through the course of evolution in response to biotic and abiotic pressure of the environments in which those animals live. The bioactive peptides released by granular glands of the anuros are the subjects of intense research in order to discover the chemical composition, the action mechanisms and the biological activities of these molecules . Several peptide molecules have been isolated and characterized from different species of anuros. Animals from the families Ranidae and Hylidae are the most studied regarding to the knowledge about these molecules. The Hypsiboas boans species is a Hilídeo, described in 1758 by Linnaeus which until this work had no reported study on their skin secretions. Knowing the peptides produced and secreted by this species is the objective of this paper. The specimens were collected on the banks of “Tinga Igarapé”, inside the “Reserva Florestal Adolpho Ducke”, Manaus, AM. The secretions were obtained by electrical stimulation , freeze dried, purified by RP-HPLC and characterized as the primary structure of the peptides by mass spectrometry (MALDI -TOF- TOF - MS / MS) , sequenced again by Edman degradation and sequencing of the genes whitch encode the peptides . The peptide profile of these species showed a variety of peptides with potential biological activity, among which seven peptides were characterized.